Implementation Of Policy Regulation And Empowerment Of Street Vendors: What Are The Benefits For Street Vendors? - Hanandini, Dwiyanti; Pramono, Wahyu (LPPM Universitas PGRI Sumatera Barat, 2022)
The Municipal Government of Padang has changed its policy towards street vendors through city government regulations by placing street vendors as part of the urban economic system that needs to be organized and empowered. So far, the government of Padang City has considered street vendors to be the cause of disorder, so it needs to be organized. This paper will explain what benefits can be obtained by street vendors from changes in the structuring and empowerment of street vendors policies implemented by the Padang city government. The study used a quantitative method with a sample of 100 street vendors. Data was collected using a questionnaire. The research was conducted in the city of Padang. The results of the study concluded that most street vendors still have not benefited from the implementation of the policy of structuring and empowering street vendors by the Padang City government, even though the street vendors see several opportunities that will arise and can be exploited to gain profits from the implementation of the policy. The Municipal Government of Padang needs to revise this policy so that street vendors will benefit more from this policy